A Randomized, Double‐Blind, Placebo‐Controlled Trial of Quetiapine in Patients with Bipolar Disorder, Mixed or Depressed Phase, and Alcohol Dependence. (27th June 2014) - Sherwood Brown, E.; Davila, Domingo; Nakamura, Alyson; Carmody, Thomas J.; John Rush, A.; Lo, Alexander; Holmes, Traci; Adinoff, Bryon; Caetano, Raul; Swann, Alan C.; Sunderajan, Prabha; Bret, Mary E.
<x xml:space="preserve">Abstract</x> Background Alcohol dependence is common in bipolar disorder (BPD) and associated with treatment nonadherence, violence, and hospitalization. Quetiapine is a standard treatment for BPD. We previously reported improvement in depressive symptoms, but not alcohol use, with quetiapine in BPD and alcohol dependence. However, mean alcohol use was low and a larger effect size on alcohol‐related measures was observed in those with higher levels of alcohol consumption. In this study, efficacy of quetiapine in patients with BPD and alcohol dependence was examined in patients with higher mean baseline alcohol use than in the prior study. Methods Ninety outpatients with bipolar I or II disorders, depressed or mixed mood state, and current alcohol dependence were randomized to 12 weeks of sustained release quetiapine (to 600 mg/d) add‐on therapy or placebo. Drinking was quantified using the Timeline Follow Back method. Additional assessment tools included the Hamilton Rating Scale for Depression, Inventory of Depressive Symptomatology–Self‐Report, Young Mania Rating Scale, Penn Alcohol Craving Scale, liver enzymes, and side effects. Alcohol use and mood were analyzed using a declining‐effects random‐regression model. Results Baseline and demographic characteristics in the 2 groups were similar. No significant between‐group differences were observed on the primary outcome measure of drinks per day or other alcohol‐related or mood measures (p > 0.05). Overall side effect burden, glucose, and cholesterol were similar in the 2 groups. However, a significant weight increase was observed with quetiapine at week 6 (+2.9 lbs [SE 1.4] quetiapine vs. −2.0 lbs [SE 1.4], p = 0.03), but not at week 12. Scores on the Barnes Akathisia Scale increased significantly more (p = 0.04) with quetiapine (+0.40 [SE 0.3]) than placebo (−0.52 [SE 0.3]) at week 6 but not week 12. Retention (survival) in the study was similar in the groups. Conclusions Findings suggest that quetiapine does not reduce alcohol consumption in patients with BPD and alcohol dependence.